Transforming growth factor beta 1 modulates electrophysiological parameters of vas deferens epithelial cells - Yi, Sheng (Kansas State University, 2013)
Transforming growth factor β1 (TGF-β1) is a cytokine that reportedly affects the severity of cystic fibrosis lung disease. The goal of this project was to define the effect of TGF-β1 on vas deferens, an organ that is universally affected in male cystic fibrosis patients. In the first study, experiments were conducted using freshly isolated porcine vas deferens epithelial cells. Primary porcine vas deferens epithelial cells exposed to TGF-β1 exhibited a significantly reduced basal transepithelial electrical resistance (Rte). TGF-β1-induced reduction in Rte was prevented by SB431542, a TGF-β receptor I inhibitor, indicating that the effect of TGF-β1 requires the activation of TGF-β receptor I. Western blot and immunohistochemistry results showed the expression of TGF-β receptor I in native vas deferens epithelia, indicating that the impaired barrier function and anion secretion that were observed in cultured vas deferens cells can likely be observed in the native context. Immunohistochemical outcomes showed that TGF-β1 exposure led to loss of organization of tight junction proteins occludin and claudin-7. These outcomes suggest that TGF-β1 impairs the barrier integrity of epithelial cells lining the vas deferens. In a parallel study that employed PVD9902 cells that are derived from porcine vas deferens, TGF-β1 exposure significantly reduced anion secretion stimulated by forskolin, forskolin/IBMX, and 8-pCPT-cAMP, suggesting that TGF-β1 affects downstream targets of the cAMP signaling pathway. Real-time RT-PCR and western blot analysis showed that TGF-β1 exposure reduced both the mRNA and the protein abundance of cystic fibrosis transmembrane conductance regulator (CFTR). Pharmacological studies showed that the inhibitory effect of TGF-β1 on forskolin-stimulated anion secretion was abrogated by SB431542 and attenuated by SB203580, a p38 mitogen-activated protein kinase (MAPK) inhibitor. These outcomes suggest that TGF-β1, via the activation of TGF-β receptor I and p38 MAPK signaling, reduces CFTR expression, and thus impairs CFTR-mediated anion secretion. Outcomes from these studies suggest that, in epithelial cells lining the vas deferens, TGF-β1 exposure leads to an impaired physical barrier and/or reduced anion secretion, which is expected to modify the composition and the maintenance of the luminal environment and thus, is expected to reduce male fertility.
Keywords: TGF; Cystic fibrosis; Vas deferens epithelia; Tight junction; Ion transport; P38 MAPK; Physiology (0719)